2015
DOI: 10.18869/acadpub.pbr.1.4.40
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of selenite-induced cataractogenesis by hydroalchoholic extract of Echium amoenum: An experimental evaluation of the Iranian traditional eye medication

Abstract: Echium amoenum is an Iranian indigenous medicinal plant. In this research the effect of hydroalchoholic extract of this plant on sodium-selenite induced cataract formation was evaluated. Fifty five white rat pups were selected and divided into six groups. In first group (control 1) no elements injected. Second group (control 2) was received normal saline on 11-18 postpartum. Hydroalchoholic extract of Echium amoenum flower (400 mg/kg/day) intraperitonealy was injected into third group. Rats in group 4 th recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In our study, lenses in the sodium selenite group had increased levels of MDA when compared to control group lenses, indicating increased lipid peroxidation in the sodium selenite group. This observation is the same as in our and other previous studies, which reported increased lipid peroxidation upon treatment with sodium selenite [ 12 , 27 , 28 ]. A. officinalis young shoots extract increased the amount of GSH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, lenses in the sodium selenite group had increased levels of MDA when compared to control group lenses, indicating increased lipid peroxidation in the sodium selenite group. This observation is the same as in our and other previous studies, which reported increased lipid peroxidation upon treatment with sodium selenite [ 12 , 27 , 28 ]. A. officinalis young shoots extract increased the amount of GSH.…”
Section: Discussionsupporting
confidence: 93%
“…In (2015) study, we showed that E. amoenum extract significantly had a protective effect on selenite-induced cataract in rat. This effect is probably associated with the antioxidant activity of this medicinal plant, resulted in inhibiting oxidative stress caused by cataract [ 12 ]. In another experiment, we assessed the preventive effects of Origanum vulgare extract, a potent antioxidant herbal medicine, on selenite-induced cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a reduction of hydroperoxide's concentration, assessed by FOX-1 assays, and an increasing value of ferric reducing antioxidant power (FRAP) in both intra and extracellular fluid were observed. This is further confirmed by in vivo studies by Noroozpour et al, which showed that the hydroalcoholic petal extract of E. amoenum had a protective effect on selenite-induced cataracts in rats [51]. Likewise, Abbasi Larki et al [68] demonstrated that the petal of E. amoenum had a protective effect on permethrin-induced rat models.…”
Section: Oxidative Stressmentioning
confidence: 73%
“…Various alcoholic extracts of the petals of Echium have demonstrated different antioxidant activity levels [15,[49][50][51][52]. E. amoenum is one of the most studied species in the genus for antioxidant activity.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Hydroalcoholic extract of Echium amoenum also elicited a protective effect against selenite-induced lens opacification in rats, in vivo. These investigators concluded that the antioxidant phytochemicals within the plant accounted for the anti-cataract activity of Echium amoenum [230].…”
Section: Plant-derived Compounds and Herbal Remediesmentioning
confidence: 99%